The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

A green approach for the selective recovery of Copper, Lead, and Tin from End-of-Life photovoltaic solder ribbons - Shun Dai; Shiyu Wang; Haochen Wang; Fengyin Zhou; Simin Xu; Yongxin Wu; Muya Cai; Xinyi Li; Shuaibo Gao; Wei Li; Bowen Deng; Dihua Wang; et al. (Waste Management, 2026)

Application of physics-informed neural networks-based hybrid prediction models in campus thermal environment prediction - Yongbo Cui; Xiaoqing Zhou; Chengliang Fan; Haonan Lin; Simin Deng (Building and Environment, 2026)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Scalable engineering of sCNC microcapsules for synergistic weed control and environmental safeguarding - Xile Deng; Liang Li; Simin Yu; Yanan Deng; Zhanghua Zeng; Lianyang Bai (Chemical Engineering Journal, 2025)

Mendelian randomization analysis reveals causal associations between autoimmune diseases and female infertility risk - Jinyuan Wang; Haojun Long; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; Ruxin Chen; et al. (Reproductive Toxicology, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Prospects and limitations of NK cell adoptive therapy in clinical applications - Yamin Deng; Chen Wu; Jintong Na; Jing Tang; Simin Qin; Zhiyong Zhang; Liping Zhong (Cancer and Metastasis Reviews, 2025)

Developing a co-benefits evaluation model to optimize greening coverage designs on university campuses in hot and humid areas - Xiaoqing Zhou; Simin Deng; Yongbo Cui; Chengliang Fan (Energy and Buildings, 2025)

Impacts of changes in climate extremes on maize yields over Mainland China - Simin Deng; Xuezhi Tan; Bingjun Liu (Food Security, 2025)

A bifunctional amylopullulanase of Streptococcus suis ApuA contributes to immune evasion by interaction with host complement C3b - Jiajia Xu; Jiaqi Zhu; Weiyao Han; Siqi Pang; Simin Deng; Long Chen; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2024)

Ambient ultrafine particles exacerbate oxygen desaturation during sleep in patients with chronic obstructive pulmonary disease: New insights into the effect spectrum of ultrafine particles on susceptible populations - Wenlou Zhang; Baiqi Chen; Yoshiko Yoda; Masayuki Shima; Chen Zhao; Xuezhao Ji; Junyi Wang; Sha Liao; Simin Jiang; Luyi Li; Yahong Chen; Xinbiao Guo; et al. (Science of The Total Environment, 2024)

Associations of occupational exposure to micro-LiNiCoMnO2 particles with systemic inflammation and cardiac dysfunction in cathode material production for lithium batteries - Yaotang Deng; Guoliang Li; Lijie Xie; Xiaoliang Li; Youyi Wu; Jiewei Zheng; Simin Xian; Jiazhen Zhou; Jiabin Chen; Yuewei Liu; Qiaoyuan Yang; Qing Wang; et al. (Environmental Pollution, 2024)

Spectroscopic method to study the effect of lightning return stroke channel expansion on atmospheric pressure - Jin Qin; Simin Xue; Ping Yuan; Zijiang Liu; Hua Yuan Shi; Tingting An; Hong Deng; Yingying An (Atmospheric Research, 2024)

Molecular characterization of a single-negative-stranded RNA virus from the rice blast fungus Magnaporthe oryzae isolate NJ39 - Hang Ding; Yao Wang; Cong Li; Simin Shuai; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

On the development and recovery of soil moisture deficit drought events - Simin Deng; Xuezhi Tan; Xuejin Tan; Xinxin Wu; Zeqin Huang; Yaxin Liu; Bingjun Liu (Journal of Hydrology, 2024)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Paper-assisted ratiometric fluorescent sensors for on-site sensing of sulfide based on the target-induced inner filter effect - Yao Lin; Simin Ye; Jinxiao Tian; Anqin Leng; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2023)

Residual behavior and dietary risk assessment of albendazole as fungicide in citrus orchards - Lihua Yang; Simin Yao; Anugerah Fajar; Austin Merchant; Jizhe Shi; Haifeng Luo; Zhaoxia Qing; Yaocheng Deng; Xiangwei Tang; Daoxin Gong; Xuguo Zhou (Food Chemistry, 2023)

Hydrogeochemistry of groundwater surrounding a pyrite mine in southern China: Assessment of the diffusive gradients in thin films technique for in situ monitoring - Yu Liu; Lezhang Wei; Hongmei Deng; Simin Hu; Xianming Xie; Dinggui Luo; Tangfu Xiao (Journal of Hydrology, 2023)

Association of multiple air pollutants with oxygen saturation during sleep in COPD patients: Effect modification by smoking status and airway inflammatory phenotypes - Wenlou Zhang; Junyi Wang; Baiqi Chen; Xuezhao Ji; Chen Zhao; Maike Chen; Sha Liao; Simin Jiang; Zihan Pan; Wanzhou Wang; Luyi Li; Yahong Chen; et al. (Journal of Hazardous Materials, 2023)

A novel narnavirus from the plant-pathogenic fungus Magnaporthe oryzae - Yuan Lin; Jia Zhou; Xuan Zhou; Simin Shuai; Rendi Zhou; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2020)